Combined effects of co-exposure to microcystin-LR and polystyrene microplastics on growth, brain pathology and thyroid hormone homeostasis in adult zebrafish - Wang Lin; Ling Liao; Ling Ling; Huimin Luo; Ying Jiang; Xinru Li; Yilong Yao; Pinhong Yang (Ecotoxicology and Environmental Safety)
The concurrent presence of algal blooms and microplastics pollution in natural water bodies poses a novel threat. However, the joint effects of microcystin-LR (MCLR) in combination with polystyrene microplastics (PSMPs) on the thyroid endocrine system of adult fish remains unclear. In our study, male zebrafish (Danio rerio) were exposed to environmentally relevant concentrations of MCLR alone (0, 0.8, 4, 20 μg/L) and a mix of MCLR and PSMPs (100 μg/L) for 60 days. Alterations in brain histology, thyroid hormone (TH) levels, and the transcription levels of hypothalamic-pituitary-thyroid (HPT)-axis genes were used to assess the thyroid function. In the MCLR-only treatment groups, we observed mild brain tissue damage characterized by glial scarring and hyperemia. The presence of PSMPs exacerbated the brain damage cause by MCLR, resulting in more pronounced ventriculomegaly and hyperemia. No significant changes in whole-body thyroxine (T4) and triiodothyronine (T3) levels were observed in the MCLR-only groups, while a significant decrease was noted in the groups co-exposed to MCLR and PSMPs. Additionally, significant alterations in crh, tshβ, ttr, trα, and trβ expression levels in the combined exposure groups provided further confirmation that MCLR and PSMPs jointly cause thyroid endocrine disruption. Our findings suggest that the fish can trigger a compensatory mechanism to maintain thyroid hormone homeostasis in response to environmentally relevant concentrations of MCLR. However, the presence of PSMPs disrupts this self-regulatory equilibrium, thereby exacerbates the thyroid endocrine disruption cause by MCLR in zebrafish.